Answer:
5
Step-by-step explanation:
This means that 9/(2x-1)=15/(3x), so 27x=30x-15. This means that 3x=15, so x=5.
2x+4=24
-4 -4
-------------
2x=20
÷2 ÷2
----------
X=10
So 10 stickers in each pack
Pemdas, so exponent before multiply
so do a^-1/2 then multiply it by 2
remember that
![x^ \frac{m}{n}= \sqrt[n]{x^m}](https://tex.z-dn.net/?f=x%5E%20%5Cfrac%7Bm%7D%7Bn%7D%3D%20%5Csqrt%5Bn%5D%7Bx%5Em%7D%20%20)
and
![x^{-m}= \frac{1}{x^m}](https://tex.z-dn.net/?f=x%5E%7B-m%7D%3D%20%5Cfrac%7B1%7D%7Bx%5Em%7D%20)
therefor,
![a^ \frac{-1}{2}= \frac{1}{a^ \frac{1}{2} } = \frac{1}{ \sqrt{a} }](https://tex.z-dn.net/?f=a%5E%20%5Cfrac%7B-1%7D%7B2%7D%3D%20%5Cfrac%7B1%7D%7Ba%5E%20%5Cfrac%7B1%7D%7B2%7D%20%7D%20%3D%20%5Cfrac%7B1%7D%7B%20%5Csqrt%7Ba%7D%20%7D%20%20)
the we multiply by 2
Answer:
26 + y
----------
9y
Step-by-step explanation:
Your using parentheses here would remove a great deal of ambiguity. Looking at your 8-y/3y + y+2/9y - 2/6y, I have interpreted it to mean:
(8-y)/3y + (y+2)/9y - (2/6)y. For example, without parentheses, your 8-y/3y might be interpreted differently, as 8 - y/(3y), or 8 - 1/3.
Looking at (8-y)/3y + (y+2)/9y - (2/6)y again, we see three different denominators: 3y, 9y and 6 y. The LCD here is 9y. Multiplying all three terms of (8-y)/3y + (y+2)/9y - (2/6)y by the LCD, we get:
3(8-y) + (y+2) + 3y. We must now divide this by the LCD:
3(8-y) + (y+2) + 3y
--------------------------
9y
Next we need to perform the indicated multiplication:
24 - 3y + y + 2 + 3y
----------------------------
9y
and then to combine like terms:
24 + 2 - 3y + y + 3y, 26 + y
---------------------------- or -----------
9y 9y